THE EXISTENCE OF LKP FANY EMBROIDERY IN THE DIGITAL ERA IN GORONTALO CITY - Rizky Abidin; Ellys Rachman; Yahya Antu (International Journal of Innovations in Engineering Research and Technology, 2023)
This research was conducted to determine the existence of LKP Fani Embroidery in the Digitalization Era. This type of research uses qualitative research methods with a descriptive approach. Qualitative research describes various phenomena and information related to the focus of research thoroughly, factually and accurately. Data sources obtained from primary data are data obtained from research sources. Data collection is done by observation, interviews and documentation. The data validity technique that researchers use is trianregulation. The results of the study concluded that, the products produced by LKP Fani Embroidery currently have not fully met consumer demand. In addition to the current competitive competition, people are also more likely to choose clothing or products outside the region or abroad that are marketed online in the marketplace. Supporting facilities are not enough to support production activities. Narrow land, minimal budget, not yet using technology that is currently used by large companies. The promotion that was carried out only using the owner’s personal FB account had stopped for several months. consumers do not know or even know the products in LKP Fani Embroidery.